Review Article -Antibiotics Resistant to Different Microorganisms - B, Sindhu; L, krishna; Chandra. N, Mahesh (International Journal of Scientific Research and Management (IJSRM), 2022)
Over a years, people mostly who were struggled with primary cause of infection and diseases by microorganisms, and utmost care has been taken that some antibiotics are highly resistant to bac- terial species and emergence of broad-range of antibiotic therapy. Broad-spectrum antibiotics have widely emerged in various ways to kill microorganisms that tend to cause illness and diseases in the human era. New resistance mechanisms are emerging and spreading worldwide. However, some bacteria may become resistant to commonly used antibiotics. Antibiotic-resistant bacteria are bacteria that are inhibited or killed by antibiotics as they can able to survive and even rapidly spread by multiplying in the human system in the presence of antibiotics. The major mechanisms interrupted in bacterial resistance are limitation of drug uptake, modification of a drug target, in- activation of a drug, and active efflux of a drug. Those bacteria are resistant to many antibiotics and they are termed Multi-resistant organisms. For example, benzylpenicillin has very little effect on most organisms in the human digestive system. Staphylococcus aureus and Neisseria gonor- rhoeae are resistant to benzylpenicillin, Methicillin-resistant Staphylococcus aureus, Vancomycin- resistant Enterococcus, Multi-drug-resistant Mycobacterium tuberculosis, Carbapenem-resistant Enterobacteriaceae. Different methods were used for detecting the antibiotic resistance to different microorganisms mainly Gram-negative bacilli, and Gram-positive bacteria. The common ways that antibiotic-resistant bacteria can be transmission in hospitals from person to person is through contact with contaminated hands of hospital staff, door handles, hospital beds, and equipment. Important ways can be followed to prevent antibiotic resistance by minimizing unnecessary over- prescribing of antibiotics by medical practitioners and maintaining proper hygiene such as hand washing by use of regular infection control.